Open spaces as the key to the integration issue of historical site reconstruction projects: a cross-cultural comparison - Qian Liu; Yiran Liu; Laura Pezzetti (Built Heritage)
Abstract The reconstruction of historical sites, while a controversial practice, has been common in both Germany and China to mitigate the cultural losses incurred during wars and subsequent redevelopment. This paper contributes to the broader discourse on reconstruction by examining the critical significance of integration between the ‘old’ and ‘new’, which means establishing a smooth and close transition between the reconstructed sites and the surrounding urban environment, as well as the key role of open space in facilitating this integration. Through morphological analysis and site surveys, the Yanghe Tower in Zhengding, China, and the Dom-Römer in Frankfurt, Germany, are compared in this paper. The comparison reveals that the integration issue related to Yanghe Tower was not adequately addressed because the key role of open space was neglected. This paper also examines the sociocultural factors that influenced the design strategies of the two projects, suggesting that future Chinese reconstruction efforts can significantly benefit from attention to the key role of historical open spaces.